Standard of Fault for Recipient and Accessory Liability - Ee, Kwong Chiew (Journal of Malaysian and Comparative Law, 2019)
Barnes v Addy is arguably one of the most important judgments in modern equity as it represented for the first time that third parties could be held personally liable to a beneficiary under a trust, through either recipient or accessory liability. These two liabilities are now commonly known respectively as ‘knowing receipt’ and ‘dishonest assistance’. There has been considerable amount of controversy relating to the standard of fault required for each form of liability resulting from two English cases decided in early 2000s, Twinsectra v Yardley and BCCI (Overseas) Ltd v Akindele. This article seeks to critically assess the development of the law on the standard of fault for each liability post-Twinsectra and Akindele, and the treatment of the law by the Malaysian courts. This article will also examine how Malaysian courts have failed to adopt a principled approach in setting the standards of fault for recipient or accessory liability.